Recurrent ovarian and fallopian tube torsion: A case report - Lili Ellison; Katherine Sinclair; Yasmin Sana (Case Reports in Women's Health, 2024)
Adnexal torsion is an emergency commonly presenting in women of reproductive age. Timely diagnosis and management are needed to preserve the ovary. Recurrence is more uncommon. This article presents a case of recurrent torsion, and reviews the literature to highlight the significance of early diagnosis and management. The case is presented of a nulliparous 31-year-old woman who presented on five occasions with symptoms of acute pain and vomiting. Adnexal torsion was suspected on clinical assessment and ultrasound scan. She was found to have left-sided isolated fallopian tube torsion twice, and tubo-ovarian torsion on two occasions. Detorsion was performed four times. Bilateral oophoropexy was performed during an emergency laparoscopy on the fourth presentation. The left ovary was conserved, but viability was doubted. She presented four weeks later with similar symptoms. An intraoperative finding was of an auto-amputated left ovary with no attachment to infudibulopelvic ligament. This ovary was removed. Operative management was performed promptly, but planned oophoropexy was delayed, and an earlier procedure may have resulted in conservation of the ovary. There is no standardised management for prevention of recurrent ovarian torsion. The benefits of oophoropexy to prevent further torsion versus risks lack evidence. There is also debate as to the method by which oophoropexy is done. There is no consensus or guideline regarding the best management approach for recurrent adnexal torsion. Further research is needed to obtain evidence to support clinicians in discussing management options with their patients.